A descriptive-contrastive analysis of Cebuano and English idioms - Mahinay, Celia Respicio 1934- (1977)
This study described and contrasted semantically equatable Cebuano and English idioms in order to help Cebuano learners of English avoid transliteration. The writer picked out Cebuano idioms from the April through September 1976 issues of the periodical Bisaya and from actual communication situations.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Typescript.
Vita
Keywords: Cebuano language -- Idioms, corrections, errors; English language -- Idioms, corrections, errors